HUBUNGAN DIAMETER PLASENTA DAN VOLUME KEHILANGAN DARAH PASCASALIN - Siska Febrina Fauziah; Ageng Septa Rini (Poltekkes Kemenkes Maluku, 2023)
Postpartum haemorrhage is still the leading cause of maternal death in the world. One of the postpartum blood loss source comes from blood vessels that open at placental implantation site at the third phase of birth. This study aims to determine the relationship between placental diameter and postpartum blood loss volume. Cross sectional study was conducted on 120 mothers whose giving birth at Rizky Anugerah Clinic and 24-Hour Maternity Hospital from April to October 2020. The placental diameter was measured from the tip of left to right side in the center of placenta using measuring tape. Meanwhile, the volume of blood loss was measured immediately after delivery using gravimetric method. The result showed that placental diameter of respondents in this study was 17 – 22 cm and 19,72 cm in average. Meanwhile the volume of postpartum blood loss was 51 – 587 ml and 212,02 ml in average. Based on statistical test, it is known that the Sig.(2-tailed) was 0,007 and the pearson correlation was 0,243. So that, we can conclude there was a correlation between the placental diameter and the volume of postpartum blood loss whereas the larger placental diameter the greater postpartum blood loss volume. Examination of placenta after it delivered includes checking its completeness, weighing its weight and measuring its diameter and thickness can not be considered as meaningless routine examination. Although variables in this study shown a low correlation, placental diameter still provide information for midwives to anticipate the occurance of postpartum haemorrhage without ignoring other factors.